2002
DOI: 10.1034/j.1399-3054.2002.1160213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti‐auxins on maturation of embryogenic tissue cultures of Nordmanns fir (Abies nordmanniana)

Abstract: The present study was conducted to improve the transition from proliferation to maturation in embryogenic cultures of Nordmanns fir. For that reason, chemicals reported to affect endogenous levels or activity of auxin were included in the growth media during maturation. The auxin antagonist PCIB reduced proliferation and promoted the development of numerous high-quality mature embryos in the tested cell lines. PCIB could not substitute for exogenously supplied ABA and the positive effect was only found when PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
1
30
3
Order By: Relevance
“…The effect of lower concentrations was less dramatic but a stimulating effect of PCIB on the development of somatic embryos was not found in the concentration range used. Our results are contrary to those of Find et al [46] and Liao et al [44] who obtained an increase in the yield and quality of somatic embryos of Abies nordmanniana and Picea morrisonicola by exogenous treatments with several auxin antagonists, including PCIB. They suggested that the effects of endogenously produced auxin may be one reason for low or failing maturation of embryogenic cultures.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The effect of lower concentrations was less dramatic but a stimulating effect of PCIB on the development of somatic embryos was not found in the concentration range used. Our results are contrary to those of Find et al [46] and Liao et al [44] who obtained an increase in the yield and quality of somatic embryos of Abies nordmanniana and Picea morrisonicola by exogenous treatments with several auxin antagonists, including PCIB. They suggested that the effects of endogenously produced auxin may be one reason for low or failing maturation of embryogenic cultures.…”
Section: Discussioncontrasting
confidence: 57%
“…PCIB has been shown to inhibit auxin-induced b-glucuronidase (GUS) expression in transgenic Arabidopsis and physiological analysis has demonstrated inhibition of the auxin effect on the growth of Arabidopsis roots [45]. PCIB was also used successfully to inhibit auxin action in the ESM of fir [46] and was found to retard proliferation and promote the development of numerous high-quality mature embryos of Abies nordmanniana [46]. PCIB used in Picea morrisonicola proliferation increased embryo production in embryogenic culture with high auxin production [44].…”
Section: Discussionmentioning
confidence: 99%
“…Find et al (2002) found that PCIB promoted the development of numerous high-quality mature embryos in embryogenic cultures of Nordmann fir (Abies nordmanniana). Agarwal et al (2006) indicated that 20 μM PCIB led to a five-fold increase in the frequency of microspore embryogenesis in cultures of B. juncea, while Zhang et al (2011) reported that 40 μM PCIB resulted in a 3.4-to 6.2-fold increase in the number of embryos in Brassica rapa.…”
Section: Discussionmentioning
confidence: 99%
“…The media include auxin (NAA), showed a lower level of forming tissue mass. Find et al (2002) considered the natural production of auxin in seeds as one of the possible causes of a failure of the maturation of somatic embryos on a maturation medium, this process slowed down or stopped the formation of ESM completely. The composition of the initiation medium was optimized for the ripe seed material (zygotic embryos were excised from the seed).…”
Section: Discussionmentioning
confidence: 99%